2015
DOI: 10.4103/1319-2442.157438
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy in adults: Experience at the Korle Bu Teaching Hospital, Accra, Ghana

Abstract: The objective of this study was to analyze nephrectomies performed in adults over a 12-year period at the Korle Bu Teaching Hospital, Accra and to compare our findings with reports from other institutions. In this retrospective study, medical records of 97 consecutive adult patients who underwent nephrectomy from January 2000 to December 2011 were reviewed. The parameters extracted included the patients' age, gender, indication for nephrectomy and the side of nephrectomy. Also considered were the histology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Similar were the findings of Badmus TA et al (12) who found the patients with the nonneoplastic lesions in 4 th decade, Mathew et al (13) and Bashir N et al (14) had majority patients of overall renal lesions in the 5 th decade, D Andualem et al (9) and Aiffa Aiman et al (18) had the patients in 4 th -5 th decade. Flank pain is the most common presenting symptom (85.5%) in our study followed by fever (76.95%), burning micturation (65.55%), hematuria and mass in loin (34.2%).…”
Section: Various Studies Comparing the Percentage Of Nonneoplastic And supporting
confidence: 76%
See 1 more Smart Citation
“…Similar were the findings of Badmus TA et al (12) who found the patients with the nonneoplastic lesions in 4 th decade, Mathew et al (13) and Bashir N et al (14) had majority patients of overall renal lesions in the 5 th decade, D Andualem et al (9) and Aiffa Aiman et al (18) had the patients in 4 th -5 th decade. Flank pain is the most common presenting symptom (85.5%) in our study followed by fever (76.95%), burning micturation (65.55%), hematuria and mass in loin (34.2%).…”
Section: Various Studies Comparing the Percentage Of Nonneoplastic And supporting
confidence: 76%
“…(10) The reported rates of nephrectomies for malignant conditions from studies in Nigeria and Ghana is 67.31 % and 54.6% respectively. (12,13) Two studies from India , Kashmir and Bijapur show that the malignant conditions are the major indication of nephrectomy and that is 89.13 % and 54.5% respectively. (14,15) The percentage of nephrectomies performed in non -neoplastic conditions is still high in the 3 rd world countries because of the non availability of free health services and of course lack of awareness of the gravity of the disease which results in late presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This is about two decades earlier than the pattern described for western countries where the peak age incidence is in the seventh decade (11,20,21). Earlier age at onset was also documented in an analysis of data from a population-based cancer registry in Morocco, North Africa, Ghana in West Africa, Kenya in East Africa and in India (22)(23)(24)(25). Reasons for this observed age-related variation is unclear but changing lifestyle and higher exposure to hazardous work environment among younger Africans may underlie this (26).…”
Section: Discussionmentioning
confidence: 66%
“…A study from Ghana, another West African country, also recorded tumor sizes with a mean diameter of 16.8 ± 4.0 cm (23). In contrast, a large population based study from Europe and a study from the United States showed that tumors ≤7 cm accounted for 58.3% and 89.7% of cases diagnosed respectively (27).…”
Section: Discussionmentioning
confidence: 99%
“…The data was taken and analyzed using a Statistical Package for Social Sciences for Windows operating system version 19. Studies showed that 85% were proven to be malignant, while 14.5% were found to be benign [12].…”
Section: Case 5 -Telecommunicationmentioning
confidence: 99%